Leadership During ERM Transition Implementation in The Public Sector - Farida Nurfitriana; Purwartiningsih Lisdiono (Jurnal Teknologi dan Manajemen, 2024)
This research aims to determine the appropriate leadership style in the public sector transition period from implementing vernacular risk management to formal risk management or ERM. This leadership style also considers leadership factors, and implementing a risk culture has become the main factor in implementing ERM in various studies. The research method uses a descriptive qualitative approach, with a research strategy in the form of case studies. The data used is primary data and secondary data. Primary data is the results of interviews with 16 respondents who are parties who participate in managing risks at the ZYX ministry. Secondary data is all internal and external data related to MRPN. The general conclusion is that Agile leadership is needed so that ZYX Ministry can adapt to the VUCA era. Leaders with agility can guide their organizations to become faster, more adaptive, and more productive. Agile Governance is the key to responsive and proactive governance.